Moderating Role of Corporate Governance on the Effect of Innovation Investment to the Financial Performance among Publicly-listed Software Outsourcing Companies in China - 孟京津; M. Perez, CPA, Ph.D, Jennifer (Pacific International Journal, 2024)
This study examines the relationship between innovation investment, corporate governance, and financial performance among publicly listed software outsourcing companies in China. Utilizing a mixed methods approach, the research integrates quantitative analysis of financial and governance data with qualitative insights from structured interviews with Chief Financial Officers (CFOs). The study explores how various corporate governance factors, such as board size, independence, meeting frequency, CEO duality, and compensation, influence the effectiveness of innovation investments in enhancing company performance. Findings indicate that while there is a positive correlation between innovation investment and financial performance, the relationship is not statistically significant. Moreover, corporate governance factors, except for board size, do not significantly moderate this relationship. The results suggest that aligning innovation strategies with strong corporate governance practices is essential but not sufficient to ensure enhanced financial outcomes. The study’s findings have practical implications for industry practitioners, policymakers, and investors, emphasizing the need for optimized governance structures to support sustainable growth in the software outsourcing sector. However, limitations regarding data reliance, sample size, and sectoral focus are acknowledged, with recommendations for future research to address these constraints and explore additional variables influencing the innovation-performance link.